The value of Cone-Beam CT-guided radiofrequency ablation in the treatment of pulmonary malignancies (≤3 cm). Issue 2 (26th February 2019) - Xiang, Zi-jun; Wang, Yi; Du, En-fu; Xu, Lin; Jiang, Bin; Li, Huili; Wang, Yun; Cui, Ning
Abstract : The aim of this study is to explore the safety and efficacy of Cone-Beam computed tomography (CBCT) guided radiofrequency ablation (RFA) in the treatment of pulmonary malignancies. Thirty-one patients with pulmonary malignant tumors (≤3 cm in diameter) were enrolled to this study. Total 43 CBCT guided RFA treatments were performed, including 7 patients undergoing multiple treatments. The target tumor puncture success rate, tumor remission rate, postoperative cumulative survival rate, tumor-free survival rate and complication rate were analyzed. All 43 CBCT guided RFA procedures successfully punctured the target tumors. Complications included five cases of pneumothorax and three cases of hemoptysis. For the 31 patients who underwent CBCT guided RFA, the 1- and 2-year cumulative survival rates were 80.6 and 54.8%, respectively. The 1- and 2-year disease-free survival rates were 54.8 and 32.3%, respectively. The 1-, 3- and 6-month remission rates were 78.4, 68.7 and 63.3%, respectively. The average cumulative radiation dose and average effective radiation dose were 194.62 ± 105.51 mGy and 5.41 ± 3.45 mSv, respectively. CBCT help to shorten the operation time, reduce the unnecessary interventions and also reduce the incidence of complications. CBCT guided RFA is one safe and efficacious treatment for pulmonary malignancies.